Managing Forest Carbon in a Changing Climate - Ashton, Mark S.; Tyrrell, Mary L.; Spalding, Deborah; Gentry, Bradford; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
The goal of this volume is to provide guidance for advanced students, land managers and policymakers seeking to understand the complex science and policy of forest carbon as it relates to tangible problems of forest management and the more abstract problems of addressing drivers of deforestation and negotiating policy frameworks for reducing emissions from forests. It is an attempt at a comprehensive state-of-the-art review, encompassing the science of carbon sequestration in forests, management of forests for carbon and other values, and the socio-economic and policy implications and challenges of managing forests for carbon. Forests are critical to mitigating the effects of global climate change because they are large storehouses of carbon and have the ability to continually absorb carbon dioxide from the atmosphere. But today, emissions from land use, land use change, and forestry, mostly due to deforestation in the tropics, are estimated at 17% of total annual global CO2 emissions, a figure larger than the transportation sector. While the basic principles of the carbon cycle are well known, there are significant uncertainties about the actual behavior of many of its sinks and sources. Much work has been done on the science of forest carbon, deforestation, and various climate policy responses, however, what is lacking is a comprehensive review of all aspects of the challenge. This book provides such a review by taking a holistic perspective on the subject. By creating a publication that outlines the research that has been done on forest carbon, pointing out what we know and what we don$1 (Bt know, and the implications for policy decisions.s
Chapter 1 Introduction -- PART I the Science of Forest Carbon -- Chapter 2 Characterizing Organic Carbon Stocks and Flows in Forest Soils -- Chapter 3 The Physiological Ecology of Carbon Science in Forest Stands -- Chapter 4 Carbon Dynamics of Tropical Forests -- Chapter 5 Carbon Dynamics in Temperate Forests -- Chapter 6 Carbon Dynamics in the Boreal Forest -- PART II Measuring Carbon in Forests -- Chapter 7 Methods of Measuring Carbon in Forests -- Chapter 8 The Role of Forests in Global Carbon Budgetting -- PART III The Management of Carbon in Forests and Forest Products -- Chapter 9 Managing Carbon Sequestration in Tropical Forests -- Chapter 10 Managing Carbon Sequestration and Storage in Temperate and Boreal Forests -- Chapter 11 Managing Afforestation and Reforestation for Carbon Sequestration: Considerations for Land Managers and Policy Makers -- Chapter 12 Role of Forest Products in the Global Carbon Cycle: From the Forest to Final Disposal -- PART IV Socioeconomic and Policy Considerations for Carbon Management in Forests -- Chapter 13 Large and Intact Forests: Drivers and Inhibitors of Deforestation and Forest Degradation -- Chapter 14 Economic Drivers of Tropical Deforestation for Agriculture -- Chapter 15 The Economic Drivers of Forest Land Use and the Role of Markets in the United States -- Chapter 16 United States Legislative Proposals on Forest Carbon -- Chapter 17 REDD+ Policy Options: Including Forests in an International Climate Change Agreement -- Chapter 18 Synthesis and Conclusions -- Glossary -- Editor Bios -- Author Bios.
Keywords: Life sciences; Endangered ecosystems; Forests and forestry; Climatic changes; Environmental management; Sustainable development; Life Sciences; Forestry; Climate Change; Environmental Management; Sustainable Development; Ecosystems